DEVELOPING TEACHING MATERIAL FOCUS ON WAVE SUBJECT USING PISA (PROGRAMME FOR INTERNATIONAL STUDENT ASSESSMENT) ON UNDERGRADUATE DEGREE PROGRAMS IN PHYSICS - Sahyar Sahyar; Wawan Bunawan (Jurnal Pendidikan Fisika, 2019)
Indonesian students' competence in solving PISA literacy-based science questions is still relatively low compared to ASIA countries and even ASEAN countries. The research aims to develop wave material teaching materials based on PISA literacy for basic Physics courses in the Unimed Physics Study Program in the first semester of 2019/2020. This type of research is a research development using the stages of Analyze Design Develop Implement Evaluate (ADDIE). PISA-based competencies include competency in explaining science phenomena, competence in evaluating and designing science experiments and competence in interpreting the data from science experiments. In the analysis phase it was found that the available wave teaching materials did not fully support the demands of PISA competence. At the design stage, wave teaching materials are arranged by emphasizing the achievement of PISA competencies. At the development stage of the teaching material is validated by the material expert and revised according to expert input. At the implementation stage, teaching materials were tested on a small group of students and revisions were made to the material aspects of the competence of scientific inquiry and data interpretation in accordance with the difficulties found in the field. At the evaluation stage teaching materials are applied to undergraduate students in Physical Education. Results obtained: there was an increase in student responses and PISA-based competencies after using the developed wave teaching materials